The Ironbridge Gorge Heritage Site and its local and regional functions - Cudny Waldemar (Bulletin of Geography. Socio-Economic Series)
The article is devoted to the issue of heritage and its functions. Based on the existing literature, the author presents the definition of heritage, the classification of heritage resources, and its most important impacts. The aim of the article was to show the functions that may be performed by a heritage site, locally and regionally. The example used by the author is the Ironbridge Gorge Heritage Site in the United Kingdom. Most heritage functions described by other authors are confirmed in this case study. The cultural heritage of the Ironbridge Gorge creates an opportunity to undertake various local and regional activities, having first of all an educational influence on the inhabitants, school youth and tourists. We must not ignore the economicinfluences, such as financing the activity of the Ironbridge Trust (the institution administering the site), generating income for local firms providing service to tourists, or for construction companies. This income helps to preserve and conserve the tangible heritage of the Ironbridge Gorge, as well as to generate jobs in heritage management, conservation and heritage tourism. Other effects of the Ironbridge Gorge Site include a socio-cultural impact or that related to sustainable development.